Mapping the Future of Human Resource Development: A Bibliometric Analysis with VOSviewer - Muhammad Rafi Dhia; Muh. Akbar (Mustard Journal De Ecobusin, 2024)
The present study intends to map the developments and future trends in Human Resource Development (HRD) using a bibliometric analysis. The publication data of highly ranked academic journals on the topic of HRD were examined with the help of VOSviewer software to reveal the major research trends, author and institutional partnerships, and the most commonly used keywords. The analysis has uncovered a number of prevailing clusters such as transformational leadership, human resource management, talent management, human resource development and performance management. The cluster of transformational leadership became very salient, as it reflects its close support with job satisfaction, employee performance, motivation, and organizational outcomes. The human resource management cluster focuses on financial performance, lean processes, and efficiency in the public sector. The role of talent management was emphasized in the hospitality sector and the rise in using evidence-based methods. The cluster human resource development deals with high performance, coaching practices and organizational citizenship behavior whilst performance management deals with employee performance, job crafting and evaluation systems. Moreover, the research discerns a growing tendency towards global collaboration, which highlights the role of global outlook in HRD research. These results give a broad perspective of the changing HRD landscape and give an orientation to the future research directions.